EMPTY ELECTRONIC STATES IN THE SODIUM TUNGSTEN BRONZES - A STUDY BY INVERSE PHOTOEMISSION SPECTROSCOPY - Allen, P; Dobson, P; Egdell, R (1985)
Empty electronic states in the sodium tungsten bronze Na 2 3WO3 have been studied by inverse photoemission spectroscopy using a novel narrow-bandpass photon detector. The empty density of states in the t2g(W:5d) band peaks about 3 eV above the Fermi energy, implying an overall t2g bandwidth greater than found in recent bandstructure calculations. © 1985.